Bricolage, Self-reflection, and Transformative Pedagogy among Student Teachers: A Case of Micro-teaching Practices for a Transformative Pedagogy - Ernest Mpindo; Matsolo Mokhampanyane (Noyam Journals, 2024)
This transformative research paper discusses individual agency and looks into how students apply critical self-reflection after being exposed to micro-teaching. When student teachers graduate to become fully trained teachers, it is required of them to have both theoretical and practical competency. Student teachers struggle to use micro-lessons as a tool to improve practice, instead, they perform micro-lessons for marks which defeats the entire purpose of conducting micro-teaching practices. This qualitative research paper adopted the Participatory Action Research (PAR) approach, underpinned by bricolage theory, which is a metaphor for research that " uses what is available to accomplish new aims and creates something out of nothing," conveniently sampled sixteen student teachers from the University of Technology in South Africa. The results demonstrated that, on a very small scale, PGCE students may use critical self-reflection as a skill to improve and address teaching concerns. Additionally, the study found that students struggle to critically evaluate themselves using a variety of media, including reflective journals and video recordings. In light of the findings, the study recommended that in a natural setting, student teachers can act as change agents. In South Africa, where most local schools are under-resourced, this paper contributes to the ongoing efforts to improve teaching as a practice using what is already available in schools.